Combined non-invasive assessment of endothelial shear stress and molecular imaging of inflammation for the prediction of inflamed plaque in hyperlipidaemic rabbit aortas - Gitsioudis, Gitsios; Wolf, Peter Georg; Missiou, Anna; Bartling, Sönke; Arica, Zeynep; Nunninger, Maximilian Martin; Erbel, Christian; Katus, Hugo; Korosoglou, Grigorios (European heart journal - cardiovascular imaging, 2017)
Aims. To evaluate the incremental value of low endothelial shear stress (ESS) combined with high-resolution magnetic resonance imaging (MRI)- and computed tomo
Online publish-ahead-of-print 24 March 2016
Gesehen am 26.06.2018